Cloud computing for rural ICT development: Opportunities and challenges - Firdhous, Mohamed; Ghazali, Osman; Hassan, Suhaidi (2013)
According to the United Nations, almost 50 percent of world population and more than 70 percent of that of developing countries are living in rural areas. Majority of this population live in poverty especially in North and sub Saharan Africa. Rural population face unique problems compared to their urban counterparts in terms of access to technologies, infrastructure, markets and social services.Experts have identified ICT as the tool for overcoming the inefficiencies in traditional methods for the empowerment of rural masses.In this paper, we study how cloud computing can be used to meet the ICT requirements for rural development in terms of opportunities and challenges of implementing and using the new technology.